Definição de um framework para projeto persuasivo aplicado a sustentabilidade - Schiefelbein, Un Hee (2019)
Gradually concern about sustainability has drawn the attention of the general population, especially regarding the conscious use of natural resources. However, there is a great distance between the user being aware of what should be done and the execution of such. Sometimes the absence of an incentive can be the cause of this, persuasive computing arises precisely for this purpose, as it is possible to influence certain behaviors through applications that send messages or reminders, ie by providing information about certain behavior the system or app can encourage decision making. Regarding sustainable habits, studies that present solutions that seek to trigger behaviors for the conscious use of resources have shown efficient results. In this sense the present work presents a set of the main persuasive strategies present in the literature and the discovery of some key strategies for the use in persuasive systems aiming at sustainability, focused on a better use mainly of electric energy, based on this was developed a conceptual framework. for the creation of persuasive applications focused on sustainable behaviors. For evaluation of the framework an application was developed that followed the steps delimited in it. The application has been tested for 120 days and the results have significant savings, as well as increased user motivation to engage in sustainable behaviors.